2001
DOI: 10.1002/fam.756
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the fire performance of electric cables (FIPEC)

Abstract: The FIPEC project is a research project funded by DG XII of the European Commission and co-5nanced by several European cable manufacturers, compounders, cable users and governmental research bodies. The FIPEC project has developed di4erent levels of testing ranging from a small-scale, cone calorimeter test procedure developed for cables and materials, a full-scale test procedure based on the IEC 60332-3, but utilising HRR and SPR measurements, to a real-scale test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 2 publications
0
52
0
Order By: Relevance
“…Cone calorimetry data on individual wire and cable compounds were not found to be simple predictors for burn performance in composite cable designs using multiple compounds in more than one layer of a construction, but simple composite (multi-layer) tests with multiple compounds provided better results. It was concluded that cone calorimetry is a useful screening tool for the cable manufacturer [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cone calorimetry data on individual wire and cable compounds were not found to be simple predictors for burn performance in composite cable designs using multiple compounds in more than one layer of a construction, but simple composite (multi-layer) tests with multiple compounds provided better results. It was concluded that cone calorimetry is a useful screening tool for the cable manufacturer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is no widespread agreement in the industry about which parameters are most meaningful. Therefore, more studies correlating burn performance in key industry tests with results of cone calorimetry on compounds are needed.Cone calorimetry on cable specimens has been successfully correlated with real-scale burn tests [4], which represents an important milestone in cable testing methodology development. Cone calorimetry data on individual wire and cable compounds were not found to be simple predictors for burn performance in composite cable designs using multiple compounds in more than one layer of a construction, but simple composite (multi-layer) tests with multiple compounds provided better results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If even just one of the wires or cables in a system is damaged or severed, the whole system suffers. The common hazards that pose a threat to these vital conductors of information and electricity are well-documented and vary depending on the type and location of the system [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, all along it was only possible to assess fire behavior by standard scale tests [9][10][11][12][13][14][15][16], from bench-scale vertical flame tests for single cable (IEC 332-1, UL 1581 VW-1) and overall fire performance test with cone calorimeter (ISO 5660) to intermediate-scale vertical flame tests for bunched cables (IEC 332-3, UL1581, UL1685, UL 1666) and UL 910 Steiner tunnel test and further to large-scale ISO Room/ Corner Test (ISO 9705), they provided but a simple grading or pass/fail criteria of the materials tested. The data obtained from these assessments apply to the behavior of the material inside the test apparatus and it is rarely possible to use such data to calculate the performance of the material in its end use environment.…”
mentioning
confidence: 99%